PENGARUH PAYLATER TERHADAP KEPUTUSAN PEMBELIAN KEMBALI PRODUK DI E-COMMERCE SHOPEE: PAYLATER EFFECT ON DECISIONS REBUYING PRODUCTS AT E-COMMERCE SHOPEE - Sarihim; Leo Alexander Tambunan (Universitas Sains dan Teknologi Komputer, 2022)
The purpose of this study was to determine the effect of paylater on product repurchase at Shopee E-commerce. This study uses quantitative methods with primary data as a reference. The population in this study is people who have bought products using Shopee Paylater more than 1 time at Shopee Indonesia and the sample is 125 people. The data collection technique used a questionnaire consisting of 25 questions in total. The analytical technique used in this study is multiple linear regression analysis by conducting validity tests, reliability tests, followed by hypothesis testing after the assumption test is met. From the analysis conducted, it can be concluded that: (1) Trust (X1) is negative towards repurchase (Y). (2) Ease (X2) has an effect on repurchase (Y). (3) security (X3) has an effect on repurchase (Y). (4) Trust (X1), convenience (X2) and security (X3) affect repurchase (Y). Based on the results of the study found the effect of trust, convenience, security on product repurchase at E-commerce shopee